The Role of Catechetics in Countering the Spread of Agnosticism in the Information Age - John Ronaldo; Yanto Paulus Hermanto; Andrew Jordan; Fajar Sentosa Pradika; Karolin Ferdianto (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2026)
The Christian community still lacks adequate knowledge in terms of literacy and in filtering social media, making them easily influenced by hoaxes. The spread of information is also suspected to compromise Christian values and even foster an attitude of indifference toward divinity. This research employs a qualitative method by reviewing literature and scholarly works that discuss the role of Catechetics and the impact of Agnosticism in the Information Era. Agnostics are generally less interested in supernatural matters such as spiritual experiences and worship rituals, but rather prioritize personal needs and ideas that are logically acceptable. The Church faces increasing demands to deliver the message of God’s Word in a contextual and refreshing manner that addresses the needs and struggles of today’s believers. Catechetics, therefore, must play a vital role in providing learning that transforms one’s worldview into a Christ-centered perspective.